The Hardiness of Adolescents in Various Social Groups - Malkin, Valerii; Rogaleva, Liudmila; Kim, Alla; Khon, Natalya (Frontiers in Psychology, 2019)
Hardiness is considered as one of the adaptation resources of personality in stressful situations, responsible for mental health preservation. Adolescents as an age group is one of the most susceptible to stress factors, so conducting research on the development of hardiness in adolescents becomes necessary. Due to difference in social conditions under which development of the hardiness of adolescents takes place, the purpose of our research was to study the hardiness of adolescents included in different social groups: 1st group which comprised of athletes, students of sports schools, which the 2nd group was made up of students of specialized schools for intellectually gifted individuals, and lastly the 3rd group was made up of students of regular schools. In total, 239 adolescents of 14-16 years old participated. The study revealed significant differences in the development of hardiness among all three groups of adolescents. The general and specific patterns of the development of hardiness components of adolescents in different social groups were identified. The article describes the main types of manifestation of hardiness and its components under different social conditions of activity and development in modern adolescents.